2010
DOI: 10.1177/030089161009600112
|View full text |Cite
|
Sign up to set email alerts
|

Image-Guided Robotic Radiosurgery as Salvage Therapy for Locally Recurrent Prostate Cancer after External Beam Irradiation: Retrospective Feasibility Study on Six Cases

Abstract: Salvage radiosurgery with CyberKnife after irradiation is feasible with low urinary and rectal morbidity. A longer follow-up and a larger number of patients are necessary to evaluate its effectiveness and optimal patient selection criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 38 publications
(36 reference statements)
5
43
0
Order By: Relevance
“…Vavassori et al published the first results on prostate re-irradiation using this system. In this preliminary retrospective case series including 6 patients treated with a total dose of 30 Gy in 5 fractions on the whole prostate gland, 2 patients remained bNED after 11.2 months of median follow-up [18]. Since then, Fuller et al published a retrospective study including 29 patients treated with a total dose of 34 Gy in 5 fractions within a median follow-up of 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…Vavassori et al published the first results on prostate re-irradiation using this system. In this preliminary retrospective case series including 6 patients treated with a total dose of 30 Gy in 5 fractions on the whole prostate gland, 2 patients remained bNED after 11.2 months of median follow-up [18]. Since then, Fuller et al published a retrospective study including 29 patients treated with a total dose of 34 Gy in 5 fractions within a median follow-up of 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Ablative hypofractionation regimens are commonly chosen for high-precision RT, which may increase the chance of killing prostate cancer cells, owing to their low alpha/beta ratio. Recently, several reports on stereotactic prostate reirradiation have been published: Vavassori et al 10 reported the preliminary results on six patients treated with Cyberknife SBRT (30 Gy in five fractions over five consecutive days). This study was later updated by Jereczek-Fossa et al: 11 complete response was obtained in six out of nine patients (without any systemic therapy) with a low toxicity profile (no rectal toxicity and few urinary events).…”
mentioning
confidence: 99%
“…To the best of our knowledge, there is only one study regarding reirradiation using EBRT. Vavassori et al (11) reported cases of reirradiation using CyberKnife ® for locally recurrent prostate cancer after primary EBRT (median dose of 80 Gy). A total dose of 30 Gy in 5 fractions was administered, and no patients experienced severe urinary or rectal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Salvage re-irradiation for recurrent prostate cancer after primary EBRT has been limited due to toxicity to adjacent organs, particularly the rectum and bladder (10). Although, certain recent studies have reported the effectiveness and safety of re-irradiation with brachytherapy for locally relapsed prostate cancer, reports of re-irradiation using EBRT are scarce (11,12). Thus, in the present study, two cases of locally relapsed prostate cancer following EBRT treated with re-irradiation using helical tomotherapy are discussed.…”
Section: Introductionmentioning
confidence: 92%